MEMPROGRAMKAN AKSES PEMBIAYAAN SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DI DESA KAREHKEL, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Rully Trihantana; Ermi Suryani; Putri Mey Dina (SAHID DEVELOPMENT JOURNAL, 2023)
Islamic Financial Institutions (LKS) and MSMEs are very important to pay attention to. This is because MSMEs are businesses that are managed by small entrepreneurs, and with small capital, but have a major contribution as one of the pillars of the Indonesian economy. On the other hand, they are vulnerable businesses due to lack of access to capital, small production capacity and relatively narrow market share. Therefore, a community service program is needed through socialization that can support the real sector and MSME businesses. This community service activity is carried out with the aim of providing knowledge and information to the public on how to develop a business based on Islamic sharia through collaboration with Islamic financial institutions. This independent service is held in Karehkel Village, Leuwiliang District Bogor Regency.